O Inventário de envolvimento paterno: estrutura teórica e ampliação de indicadores de validade e de precisão - Santis, Ligia de (2020)
Father involvement is influenced by psychosocial factors in the lives of parents and children and is associated with the healthy development of children and the well-being of parents. A model of the interpersonal processes related to this construct, and a psychometrically sound instrument to measure father involvement would contribute to improving the quality of professional work in this area, in Brazil. The Inventory of Father Involvement (IFI) has been adapted for use in Brazil (the IFI-BR), and although initial evidence of its validity has already been demonstrated, further information is needed to support evidence-based practice. Thus, the objectives of the present study were to: (a) continue to investigate the validity of the IFI-BR, examining additional evidence of the internal validity of the instrument, and its relation with other constructs, (b) compare results for fathers who responded to the instrument in-person, or on-line, and (c) evaluate a processes model of father involvement. Participants included 1,085 fathers with children in early childhood education and primary school settings. They completed the IFI-BR, a sociodemographic questionnaire, the Perceived Stress Scale, and two of the following measures: a second measure of father involvement (the Paternal Engagement Questionnaire or the Parenting Practices Inventory), the Marlowe-Crowne Social Desirability Scale, the Social Skills Inventory - Del Prette, and the Preschool and Kindergarten Behavior Scale. In Study 1, estimators of the precision and evidence of the internal validity (using factor analysis) of the IFI-BR were analyzed, for two samples: (a) fathers with children in early childhood education settings and (b) fathers with children in grades one to five. Based on these results, suggestions were made for changing some of the items. In Study 2, evidence for the internal validity of the modified version of the IFI-BR was examined, confirming the nine-factor structure of the American version of the IFI with the Brazilian sample of fathers with children in preschool through to grade five. The precision of the nine factors varied from 0,611 ≤ ω ≥ 0,779. In Study 3, evidence was found with respect to: (a) convergent validity, and (b) associations with related constructs, for the IFI-BR. In Study 4, initial evidence of validity based on the internal structure of the on-line version of the measure was observed, confirming the American structure of the IFI, with adequate estimators of precision (0,608 ≤ ω ≥ 0,838). However, some differences were found in the level of father involvement and in the sociodemographic profile of each group of fathers. Finally, in Study 5, the interpersonal process model was evaluated, confirming that some demographic variables and the fathers’ social skills predict the quality of father involvement. Fathers’ stress seems to act both as a predictor and as an outcome of father involvement. These results indicate the potential of the IFI-BR in assessing the quality of father involvement with Brazilian fathers of children from early childhood education through to grade five, for both the in-person and on-line versions. In future studies, in addition to examining scores on the IFI-BR for fathers in contexts that may negatively affect the quality of their paternal involvement, efforts are also needed to capture information about the psychometric properties of the items and evidence based on: (a) criterion validity, (b) experimental and quasi-experimental studies, (c) response processes, and (d) consequences of testing. This instrument, combined with greater knowledge about interpersonal processes related to father involvement, in Brazil, will contribute to the quality of research work and professional interventions to support father involvement.